Violation of the Principles of International Humanitarian Law and War Ethics in the Dynamics of the Iran-Israel Shadow War Conflict - Septino, Rofid Nadhil (Dinasti Research, 2021)
This study examines violations of international law and the principles of just war ethics within the shadow war dynamics between Iran and Israel. This conflict unfolds through covert actions such as the assassination of scientists, cyberattacks on nuclear facilities, and other clandestine operations aimed at undermining Iran's strategic capabilities. The research is motivated by the lack of comprehensive studies that integrate international humanitarian law and ethical frameworks in the context of undeclared conflicts. Using a qualitative approach through literature review, this study identifies various violations of international law, including breaches of sovereignty, extrajudicial killings, and disproportionate attacks. Ethically, these actions violate the principles of just cause, proportionality, precaution, and distinction. The findings indicate that the nature of shadow war presents a serious dilemma for the enforcement of international legal norms due to its secrecy, lack of verification, and persistent denial by state actors. This study aims to offer a new normative perspective on how the international community interprets and responds to asymmetric conflicts such as the Iran–Israel case, while encouraging a re-evaluation of the application of legal and ethical standards in contemporary geopolitical landscapes.